Current problems of running training of qualified track and field jumpers - Salamatov, M. B. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identifying current problems in the running training of highly qualified track and field jumpers specializing in the running triple jump, identifying areas for improvement in this jumping discipline.